99% perspiration : a new working history of the American way of life - Chandler, Adam (Pantheon Books, 2025)
"An enlightening and entertaining interrogation of the myth of American self-reliance and the idea of hard work as destiny "Genius is one percent inspiration and ninety-nine percent perspiration." This phrase, arguably Thomas Edison's most famous quote, has been drilled into the minds of generations of Americans. A fairly straightforward iteration of the idea that innovation, discovery, and ingenuity are the result of drive and grit above all, it has also come to represent much darker myths: that hard work always leads to success and that achievement is the product of individuals and not communities. In this model, those who come out on top are there because they earned it, and everyone else needs to buckle down, glove up, and, maybe one day, they'll get there too. As the wealth gap widens, communities crumble, and Americans work more for less, Adam Chandler raises the question: What happens when perspiration isn't enough? To answer it, he crisscrosses the country interviewing mayors, teachers, generals, pastors, construction workers, and entrepreneurs, to reveal just how untenable relying on "perspiration" as a strategy has truly become. He also delves into America's past to reveal how our government, education system, and culture at large have woven the idea of meritocracy deep into the fabric of American society and how some of history's most famous so-called bootstrappers really built their wealth. From George Washington to Seattle, Washington, Jay Gatsby to Bill Gates, 99% Perspiration unpacks the misguided obsession with hard work that has come to define both the American dream and nightmare, offering insight into how we got here and hope for where we may go"--